Influence of digital environment on the cognitive function of schoolchildren and students - E. A. Avdeeva; O. A. Kornilova (Кардиоваскулярная терапия и профилактика)
Aim. To analyze studies on the influence of digital environment on cognitive development of schoolchildren and students.Material and methods. To achieve this aim, pedagogical research methods were used, which include work with literature on the stated topic, analysis of their content, logical generalization, citation, bibliographic listing, and annotation were used. An important role was played by generalization method and identification of patterns of longterm digital environment influence on a person.Results. An analysis of the literature has shown that digital environment influence on cognitive development of schoolchildren and students is the subject of research by many authors. One group of scientists considers the digital environment to be a neutral factor in relation to younger generation cognitive function. But, in parallel, studies are being conducted in which scientists has the opposite position. This group includes Russian and Western scientists from Harvard, Oxford, Manchester, Sydney Universities and King’s College London. Over the past twenty years, from 1998 to 2018, they have conducted studies on the impact of electronic devices and the Internet on cognitive functions of the younger generation. In total, 139 papers were published, in which the authors studied the effect of digital environment on cognitive changes from the standpoint of psychology, psychiatry, neurobiology, and other sciences. These studies proved that digital environment affects, first of all, the change in the brain, which acts as a bioplatform for the formation of cognitive functions in schoolchildren and students. And a change in cognitive functions cannot but affect the cognitive processes of attention, memory, thinking, as well as the skills necessary for cognition.Conclusion. The presented data from Russian and foreign studies revealed facts proving that the digital environment is a factor that changes the cognitive development in children, adolescents and students. The use of the Internet as an ultra-easy way to obtain information leads to the fact that a person blurs the boundaries between his own capabilities and the capabilities of electronic devices, attributing to himself their superpowers.